The Influence of Measurement Game Tools on Problem Solving Ability in Children Ages (3-4) Years - Mutiara Salsabillah; Febriyanti Utami (UPI Kampus Cibiru, 2023)
This study aims to see the effect of measurement game tools on early childhood problem-solving abilities. The method used in this study is pre-experimental design with the design of the one-shot case study. This study was conducted on children aged (3-4) years at Rumah Belajar Ceria Palembang with a sample of 12 children. The sampling technique uses purposive sampling technique. Data collection techniques are carried out with observation techniques to see children's problem-solving abilities. The data analysis used in this study used inferential statistics. The normality test is performed using the Shapiro Wilk Test and the homogeneity test is performed using the Hartley Test. Hypothesis testing shows that the results of the One Sample T-test have a significant value of 0.357. According to the criterion if a significant value 0.05 means that Ho is rejected and Ha is accepted. Thus, it can be concluded that the Measurement Game Tool can have an influence on the problem-solving ability of children aged (3-4) years at Rumah Belajar Ceria Palembang. This research can provide input to social institutions engaged in education to pay more attention to facilities that can help optimize the learning process, so that children do not experience delays in reaching the stage of developmental achievement according to their age.